2016
DOI: 10.1115/1.4033792
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically Coupled Combustion of Liquid Fuel Droplets

Abstract: The dynamics of oscillatory flames is relevant to acoustically coupled combustion instabilities arising in many practical engineering systems. This paper reviews fundamental studies that pertain to the combustion of single liquid fuel droplets in an acoustically resonant environment. This flow field is not only an idealized model for the study of the fundamental interaction of reactive, evaporative, acoustic, and other transport-based timescales, but it may also be used to identify relevant phenomena in more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(160 reference statements)
0
7
0
Order By: Relevance
“…The present work builds upon prior studies of the acoustically coupled droplet combustion of neat fuels (Sevilla-Esparza et al. 2014; Karagozian 2016; Bennewitz et al. 2018) and liquid nanofuel mixtures (Sim et al.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The present work builds upon prior studies of the acoustically coupled droplet combustion of neat fuels (Sevilla-Esparza et al. 2014; Karagozian 2016; Bennewitz et al. 2018) and liquid nanofuel mixtures (Sim et al.…”
Section: Introductionmentioning
confidence: 91%
“…In the past, our group at UCLA has explored acoustically coupled combustion of liquid neat fuel and nanofuel droplets (Sevilla-Esparza et al. 2014; Karagozian 2016; Bennewitz et al. 2018; Sim et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, there was a little observable change in gasification rate when droplet was stationed at velocity node. Further, the droplet diffusion flames were found to be most responsive at low excitation frequencies (~5–330 Hz) 24 , 40 44 while they exhibited diminished response at higher forcing frequencies (>400 Hz). This indicates that oscillation mechanisms in combusting droplet exhibit multi-parameter dependence and hence provide an innovative means of manipulation at the droplet scale, which form a sub-grid elements of any gel spray based combustion strategy.…”
Section: Introductionmentioning
confidence: 97%
“…A fundamental understanding of oscillatory droplet combustion is also crucial from an application viewpoint given its relevance to combustion instabilities 40 – 43 in liquid rocket engines. Interestingly, previous studies have shown that the pure fuel (ethanol, methanol) droplet flames are also susceptible to oscillations when subjected to external acoustic excitation either through travelling 24 , 44 or standing pressure waves 40 – 43 . In the latter case, an increase in droplet burn rate by as large as ~15% under normal gravity conditions has been reported when the sound pressure level exceeded ~135 dB and droplet was placed near pressure node.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet combustion experiments have also been conducted on ethanol and their blends with gasoline and diesel [13][14][15][16]. It is well understood that burning the mixtures of alcohol/alkane results in disruptive behavior due to significant volatility differential between the fuel components [17].…”
Section: Introductionmentioning
confidence: 99%